IDENTIFIKASI KARAKTER WIRAUSAHA PADA USAHA ANYAMAN AKAR KELADI AIR MEGA MAKMUR SUNGAI AMBAWANG - Dewi Roani; Nuraini Asriati; Sri Buwono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research was conducted with the aim of identifying entrepreneur character in the business of waven roots mega makmur, based on the theory of Daryanto (2012). The object of this research is Mrs. CW as the business owner, which is located on Selat Panjang street Sungai Ambawang, Kubu Raya district. The subject in this study is Mrs. CW as the business owner and Mrs. Rohana, one of her employess. The data were collected using a direct communication techniques such as interviews, documentary study techniques, and direct observation techniques. The research data collection use a observation sheets, interview guideline, and observation worksheets. The data in this study are of primary data and secondary data. And then, the data processed using descripsive analysis method. Based on the result of the analysis of the research conducted, it can be concluded that Mrs. CW have a six entrepreneur character according to Daryanto, there is self confidence, tolerance for risk, opportunity obsession, creativity, responsibility, and having high energy level. Keywords: Entrepreneur Character, the Business of Waven Roots, Small Business